Infotainment as media communication neo-genre: functional and stylistic analysis - Chepornyuk , Anastasiia (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article is devoted to the functional-stylistic analysis of the new genre of Ukrainian television news – infotainment. The author emphasizes that this genre is currently actively developing in the field of national television. In addition, it has a number of specific features inherent only to it. On the example of the TV program "Абзац!" on the New Channel and "M1 News" on the M1 channel the author provides an analysis of the broadcasting media specifics in the television programs of the infotainment genre. Infotainment – literally "infotainment = information + entertainment" – is a diffuse genre, which emerged as functional mix of two genres – informational and entertainment. The essence of the infotainment news is laying in the presentation of official news in an amusement way. The history of infotainment establishment is related not only to the globalization of television, but also to the change in information space paradigm in general. This genre emerged in the American mediaspace in the 80’s of the 20th century and, with the help of the globalization process, gradually expanded its borders therefore it became popular outside the United States. In addition, the infotainment changed its format to the needs of the Ukrainian viewer that gave it the unique features that distinguish this genre not only among other types of news, but also among similar foreign prototypes. Among such features the author distinguish: conversational style of speech, the use of a large number of stylistic trails, the irony of discourse, emotional and expressive presentation of the material, versatility of the video and the free choice of thematic content. Due to these features, the Ukrainian infotainment as neo-genre is gaining popularity among recipients. As a result, it was proved that the infotainment exists on the Ukrainian television and has its own linguistic and stylistic features that require attention not only from journalists, but also by linguists, in particular medialinguists. The bright example of studied programs shows that such a genre enriches not only the content of the television media space, but also the language of the recipients by the innovative lexical units.